2017
DOI: 10.1186/s12859-016-1439-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic prediction with epistasis models: on the marker-coding-dependent performance of the extended GBLUP and properties of the categorical epistasis model (CE)

Abstract: BackgroundEpistasis marker effect models incorporating products of marker values as predictor variables in a linear regression approach (extended GBLUP, EGBLUP) have been assessed as potentially beneficial for genomic prediction, but their performance depends on marker coding. Although this fact has been recognized in literature, the nature of the problem has not been thoroughly investigated so far.ResultsWe illustrate how the choice of marker coding implicitly specifies the model of how effects of certain all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 29 publications
(68 reference statements)
0
85
1
Order By: Relevance
“…Marker scores are typically assigned as either presence (or absence) of the reference, major, or minor allele, which may or may not be biologically relevant. While it has been noted that the two different marker encoding methods do not result in the same contrasts of genotypic classes (He et al ., 2015; Martini et al ., 2016, 2017), coding does not affect the least squares model fit (Zeng et al ., 2005; Álvarez-Castro and Carlborg, 2007). Álvarez-Castro and Carlborg (2007) show that there exists a linear transformation to shift between multiple parameterizations using a change-of-reference operation (see Appendix 3).…”
Section: Subfunctionalization Epistasismentioning
confidence: 99%
See 1 more Smart Citation
“…Marker scores are typically assigned as either presence (or absence) of the reference, major, or minor allele, which may or may not be biologically relevant. While it has been noted that the two different marker encoding methods do not result in the same contrasts of genotypic classes (He et al ., 2015; Martini et al ., 2016, 2017), coding does not affect the least squares model fit (Zeng et al ., 2005; Álvarez-Castro and Carlborg, 2007). Álvarez-Castro and Carlborg (2007) show that there exists a linear transformation to shift between multiple parameterizations using a change-of-reference operation (see Appendix 3).…”
Section: Subfunctionalization Epistasismentioning
confidence: 99%
“…This transformation does not hold when marker effects are considered random, where the interaction effect is subject to differential shrinkage depending on the marker coding and orientation (Martini et al ., 2017, 2018). As such, orienting markers to capture functional allele relationships may be crucial for optimizing genomic prediction including epistasis.…”
Section: Subfunctionalization Epistasismentioning
confidence: 99%
“…This includes BGLR (Pérez and de los Campos 2014), sommer (Covarrubias-Pazaran 2016) and rrBLUP (Endelman 2011), as well as an efficient implementation for solving the mixed model (Henderson 1975) in the traditional GBLUP model (Meuwissen et al 2001; VanRaden 2008) that is assuming known heritability and is using the R-package RandomFieldsUtils (Schlather et al 2019b) for the matrix inversion. Inputs for these packages such as the different pedigree and genomic relationship matrices (VanRaden 2008; Legarra et al 2014; Martini et al 2017) can be derived via highly efficient and fully-parallelized bit-wise matrix multiplications (R-package miraculix (Schlather et al 2019a)). Non of the mentioned packages, however, is required to execute simulations in MoBPS.…”
Section: Methodsmentioning
confidence: 99%
“…Then, a small value is added to the diagonals of G to make it non‐singular (Vela‐Avitúa, Meuwissen, Luan, & Ødegård, ). It can be shown that centring the columns of M has no effect on the BLUPs of the substitution effects and thus will also not affect the BLUP of a i − ai (Martini et al., ; Strandén & Christensen, ) . Scaling on the other hand, results in a GARM that unequally weights the IBS matrices across the loci.…”
Section: Theorymentioning
confidence: 99%